Temporal semantic compression for video browsing - Adams, Brett; Greenhill, Stewart; Venkatesh, Svetha (ACM Press, 2008)
We present a video browsing approach, termed Temporal Semantic Compression (TSC) that uses automated measures of interest to support today's foraging behaviours. Conventional browsers 'compress' a video stream using simple 2x or 8x fast-forward. TSC browsers dynamically filter video based on a single user gesture to leave out more or less of the boring bits. We demonstrate a browser with an example interest measure, derived from an automated estimate of movie tempo, to forage in terms of narrative structures such as crises, climaxes, and action sequence book-ends. Media understanding algorithms facilitate browsing, and interactivity enables the human-in-the-loop to cope when those algorithms fail to cross the semantic gap.